2016
DOI: 10.1007/s00418-016-1516-6
|View full text |Cite
|
Sign up to set email alerts
|

Giant crystals inside mitochondria of equine chondrocytes

Abstract: The present study reports for the first time the presence of giant crystals in mitochondria of equine chondrocytes. These structures show dark contrast in TEM images as well as a granular substructure of regularly aligned 1–2 nm small units. Different zone axes of the crystalline structure were analysed by means of Fourier transformation of lattice-resolution TEM images proving the crystalline nature of the structure. Elemental analysis reveals a high content of nitrogen referring to protein. The outer shape o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The CIBs found only in M. cavernosa and P. strigosa were inconsistently associated with LN lesions in the BBW, and their function is unknown. Diverse CIBs (e.g., organic crystalline metabolites) are often found in normal organisms (Edwardson and Christie, 1978;Nürnberger et al, 2017) and while the CIBs reported here are similar in ultrastructural appearance to the kalisomes in the gastrodermis of coral larvae (e.g., Pocillopora damicornis) (Clode and Marshall, 2002), they could be crystalline inclusions resembling aragonite calcium carbonate (Hayes and Goreau, 1977), and still have to be analyzed chemically. When crystallized in the laboratory at pH 8.0, the coral chromoprotein pocilloporin forms a mauve tetrahedron (Beddoe et al, 2003) reminiscent of the CIBs noted here, but it is not known whether this process would occur in corals in situ.…”
Section: Discussionmentioning
confidence: 62%
“…The CIBs found only in M. cavernosa and P. strigosa were inconsistently associated with LN lesions in the BBW, and their function is unknown. Diverse CIBs (e.g., organic crystalline metabolites) are often found in normal organisms (Edwardson and Christie, 1978;Nürnberger et al, 2017) and while the CIBs reported here are similar in ultrastructural appearance to the kalisomes in the gastrodermis of coral larvae (e.g., Pocillopora damicornis) (Clode and Marshall, 2002), they could be crystalline inclusions resembling aragonite calcium carbonate (Hayes and Goreau, 1977), and still have to be analyzed chemically. When crystallized in the laboratory at pH 8.0, the coral chromoprotein pocilloporin forms a mauve tetrahedron (Beddoe et al, 2003) reminiscent of the CIBs noted here, but it is not known whether this process would occur in corals in situ.…”
Section: Discussionmentioning
confidence: 62%
“…The study of Caldwell et al 26 was in agreement with these observations, who also demonstrated the presence of ICIs in NAFLD. In a recent study by Nürnberger, et al 61 the authors revealed ICIs of equine chondrocytes were proteinaceous in nature, detecting the proteinrelevant elements nitrogen, sulphur and phosphor by means of energy-filtered TEM. It has been postulated that such crystals in hibernating animals and oocytes may represent a form of protein storage, however in human HPCs, the presence and frequency of ICIs is considered an indication of mitochondrial degeneration 34 .…”
Section: Discussionmentioning
confidence: 99%